2011
DOI: 10.1007/s00267-011-9647-y
|View full text |Cite
|
Sign up to set email alerts
|

TMDL Implementation in Agricultural Landscapes: A Communicative and Systemic Approach

Abstract: Increasingly, total maximum daily load (TMDL) limits are being defined for agricultural watersheds. Reductions in non-point source pollution are often needed to meet TMDL limits, and improvements in management of annual crops appear insufficient to achieve the necessary reductions. Increased adoption of perennial crops and other changes in agricultural land use also appear necessary, but face major barriers. We outline a novel strategy that aims to create new economic opportunities for land-owners and other st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 90 publications
0
20
0
Order By: Relevance
“…Across the world, ever greater scrutiny is being focused on the sources of P entering rivers and the effectiveness of remediation measures 1,2 . In the U.S., total maximum daily loads (TMDLs) 3 have been implemented to attain target total phosphorus (TP) water quality criteria, through control of both point and non-point sources 4,5 . Setting TMDLs and identifying remedial options relies on appropriate and accurate apportionment of P loads across the watershed.…”
Section: Introductionmentioning
confidence: 99%
“…Across the world, ever greater scrutiny is being focused on the sources of P entering rivers and the effectiveness of remediation measures 1,2 . In the U.S., total maximum daily loads (TMDLs) 3 have been implemented to attain target total phosphorus (TP) water quality criteria, through control of both point and non-point sources 4,5 . Setting TMDLs and identifying remedial options relies on appropriate and accurate apportionment of P loads across the watershed.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies involving a participatory approach to spatial planning and modeling have found this to be an effective way to address highly complex and contentious problems compared with traditional planning approaches [24]. Integrating spatial information into the model was not possible using the Stella ® platform, but this represents a future key direction for the heat and human health modeling work.…”
Section: Lessons Learned In the Model-building Process And Their Applmentioning
confidence: 99%
“…Water quality initiatives are often hampered by limited farmer participation which has in turn been shown to be hindered by limited outreach capacity and inflexible policy (Lemke et al 2010, Jordan et al 2011. Facilitating broader farmer participation requires understanding of comprehensive farmer perspectives in order to 'calibrate' appropriate and effective programming.…”
Section: Introductionmentioning
confidence: 99%